Impact Characteristics Describing Concussive Injury in Youth - Dawson, Lauren (Université d'Ottawa / University of Ottawa, 2016)
The incidence of concussive injury has continued to arise annually with up to 3.8 million concussions reported per year (Thurman 1999) and 15% of these injuries occurring with persistent symptoms (Kraus and Chu, 2005). Few studies have examined the differences between youth and adult concussion (Yeates et al, 2012; Gosselin et al, 2010) therefore it is unknown whether youth and adults pose a similar risk of sustaining a concussion following impact. For this reason, the purpose of this study is to determine if differences exist in the dynamic response of the head and brain tissue deformation characteristics between children and adolescents for falls in comparison to adult data which have resulted in concussive injuries. Patient data was collected from emergency room hospitals across Canada. After exclusion criterion was applied, 11 child and 10 adolescent falls were reconstructed using mathematical (MADYMO) model, physical model (Hybrid III Headforms) and finite element modelling. Both groups were compared to each other as well as an adult group collected by Post et al (2014b) using a one-way ANOVA and Welsh test. The results of this study show that the children produced the lowest values for all variables when compared to the adolescents and adults whereas the adolescents produced the largest (with the exception of MPS where the adolescent and adult MPS was the same). Although all results were above the suggested thresholds for risk of concussive injury, the youth produced the lowest brain tissue strain yet still suffered a concussion. This is important to note as it may suggest that children are at an increased risk of injury at a lower brain tissue strain level. Understanding the differences in parameters influencing concussive injury may aid researchers in comprehending the unique risk for youth at difference ages. This information would be useful in terms of protective equipment design, promoting safe play in games and management of patients following injury.
Keywords: Biomechanics; Concussion; mTBI; Youth Concussion; Head Impact; Hybrid III Headform